Extraordinary exposed in early motherhood - a qualitative study exploring experiences of mothers with type 1 diabetes - Berg Marie; Sparud-Lundin Carina (BMC Women's Health, 2011)
Abstract Background Women with type 1 diabetes face several challenges during pregnancy, childbirth and in relation to breastfeeding. It is therefore of utmost importance to consider their need for specific support, early postpartum as well as in daily life after discharge from maternity care. Few studies have investigated these aspects of healthcare. The aim of this study was to explore experiences after childbirth regarding breastfeeding, glycemic control, support and well-being in women with type 1 diabetes. Methods A hermeneutic reflective life world research approach was used in this qualitative study. Data was gathered through audio-recorded focus group discussions and individual interviews with 23 women with type 1 diabetes, 6-24 months after childbirth. After verbatim transcription, the text was analyzed in order to identify themes of meaning and a conclusive interpretation of the explored phenomenon. Results Experiences of extraordinary exposure challenged the women with type 1 diabetes in their transition to early motherhood. The exposure included a struggle with breastfeeding, although with a driving force to succeed. Everyday life was filled with uncertainty and unpredictability related to one's own unstable glycemic control and the women down-prioritized their own needs in favor of the child. A feeling of being disconnected from professional care further contributed to the experiences of extraordinary exposure. Conclusion In early motherhood women with type 1 diabetes have a great need for support in managing daily life postpartum, which requires contemporary approaches to overlap insufficient linkage between health care professionals in maternity and child health care, and diabetes care.